Car following with an inertia-oriented driving technique: A driving simulator experiment. (August 2022) - Tenenboim, Einat; Lucas-Alba, Antonio; Melchor, Óscar M.; Toledo, Tomer; Bekhor, Shlomo
Highlights: All drivers adopted the same car-following strategy in the pre-test. The experimental group easily learned to Drive to keep Inertia (DI) in a DI simulator. DI participants eco-drove (less speed variations and fuel consumption) in the post-test. A group of 8 virtual cars required less road space following a DI driver. Abstract: Background: For many decades, car-following (CF) and congestion models have assumed a basic invariance: drivers' default driving strategy is to keep the safety distance. The present study questions that Driving to keep Distance (DD) is a traffic invariance and, therefore, that the difference between the time required to accelerate versus decelerate must necessarily determine the observed patterns of traffic oscillations. Previous studies have shown that drivers can adopt alternative CF strategies like Driving to keep Inertia (DI) by following basic instructions. The present work aims to test the effectiveness of a DI course that integrates 4 tutorials and 4 practice sessions in a standard PC computer designed to learn more adaptive driving behaviors in dense traffic. Methods . Sixty-eight drivers were invited to follow a leading car that varied its speed on a driving simulator, then they took a DI course on a PC computer, and finally they followed a fluctuating leader again on the driving simulator. The study adopted a pretest-intervention-posttest design with a control group. The experimental group took the full DI course (tutorials and then simulator practice). The control group had access to the DI simulator but not to the tutorials. Results . All participating drivers adopted DD as the default CF mode on the pre-test, yielding very similar results. But after taking the full DI course, the experimental group showed significantly less accelerations, decelerations, and speed variability than the control group, and required greater CF distance, that was dynamically adjusted, spending less fuel in the post-test. A group of 8 virtual cars adopting DD required less space on the road to follow the drivers that took the DI course.